Opinion towards Applications of ICT and Problems Faced by KVK Extension Personnel - Arjun Sulibhavimath; Preeti Sharma (Indian Journal of Extension Education, 2018)
The present study entitled “Opinion towards applications of ICT and problems faced by KVK extension personnel” was conducted in Punjab and Karnataka states. The objective of the study was to explore the opinion and problems faced by the KVK extension personnel in using ICT for acquiring and disseminating the knowledge. Fifty per cent of KVKs were randomly selected from both the states. From Punjab, out of 17 KVKs nine were selected and from Karnataka, out of 30 KVKs fifteen KVKs were selected. All the extension personnel in position at the time of investigation were taken from the selected KVKs. Thus 51 respondents from Punjab and 73 respondents from Karnataka, total of 124 respondents were selected for the study. The structured interview schedule was used to collect the data. Most of the respondents had positive opinion towards the use of ICTs for acquiring and disseminating knowledge to farmers. All the respondents were agreed upon various benefits of ICTs. Inadequate training on ICT tools, lack of communication infrastructure and lack of sufficient number of computers were considered as major problems by majority of the respondents. It is suggested to provide more trainings on ICT and sufficient budget to improve ICT infrastructure. Use of advanced ICT should be promoted.